K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 6 2022

Do \(2\le a\le6\Rightarrow\sqrt{a-2}\ge0;\sqrt{a-2}+2\ge0;\sqrt{a-2}-2\le0\)\(\sqrt{a+4\sqrt{a-2}+2}+\sqrt{a-4\sqrt{a-2}+2}=\sqrt{\left(a-2\right)+4\sqrt{a-2}+4}+\sqrt{\left(a-2\right)-4\sqrt{a-2}+4}=\sqrt{\left(\sqrt{a-2}+2\right)^2}+\sqrt{\left(\sqrt{a-2}-2\right)^2}=\left|\sqrt{a-2}+2\right|+\left|\sqrt{a-2}-2\right|=\sqrt{a-2}+2-\left(\sqrt{a-2}-2\right)=4\left(đpcm\right)\)

28 tháng 6 2022

\(\sqrt{a-2+4\sqrt{a-2}+4}+\sqrt{a-2-4\sqrt{a-2}+4}\)

\(\Leftrightarrow\sqrt{\left(\sqrt{a-2}+2\right)^2}+\sqrt{\left(\sqrt{a-2}-2\right)^2}\)

\(\Leftrightarrow\left|\sqrt{a-2}+2\right|+\left|\sqrt{a-2}-2\right|\)

Theo BĐT Cosi ta có \(\left|\sqrt{a-2}+2\right|+\left|\sqrt{a-2}-2\right|\ge\left|\sqrt{a-2}+2+2-\sqrt{a-2}\right|=4\)

Dấu ''='' xảy ra khi 2 =< a =< 6